2023
DOI: 10.3390/v15040865
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Respiratory Virus Co-Infections: A Systematic Review of the Literature

Abstract: Τhe COVID-19 pandemic highly impacted the circulation, seasonality, and morbidity burden of several respiratory viruses. We reviewed published cases of SARS-CoV-2 and respiratory virus co-infections as of 12 April 2022. SARS-CoV-2 and influenza co-infections were reported almost exclusively during the first pandemic wave. It is possible that the overall incidence of SARS-CoV-2 co-infections is higher because of the paucity of co-testing for respiratory viruses during the first pandemic waves when mild cases mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 124 publications
4
21
0
Order By: Relevance
“…We can see high correlation coefficients between daily positive COVID patient count and the number of patients with positive RSV (0.38 with a p -value of 0.0003). This could be because the viruses peaked in the community around the same time and because people were co-infected ( 39 , 40 ). Additionally, we can see that the number of people, and the number of positive COVID patients has a correlation coefficient of 0.22.…”
Section: Resultsmentioning
confidence: 99%
“…We can see high correlation coefficients between daily positive COVID patient count and the number of patients with positive RSV (0.38 with a p -value of 0.0003). This could be because the viruses peaked in the community around the same time and because people were co-infected ( 39 , 40 ). Additionally, we can see that the number of people, and the number of positive COVID patients has a correlation coefficient of 0.22.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that mortality is associated with ICU and even more so with nosocomial infection [ 19 , 20 ]. Many cases require hospitalization, and with preexisting diseases, the patients have a greater possibility of coinfections, mainly RSV and FLUAV [ 14 , 21 , 22 ]. Similar studies showed an increased risk of death associated with coinfection [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SARS-CoV-2 and other respiratory viruses varied throughout the COVID-19 pandemic waves with declines in FLUAV and FLUBV, RSV, HRV, and EV infections, which are the most commonly described [ 6 , 17 , 23 ]. Other viruses such as HAdV, HPIV, and hMPV were less detected compared to previous years, even during the winter season when these viruses commonly present higher rates of detection [ 17 , 22 , 24 ]. HRV was the main pathogen to substantially cocirculate with SARS-CoV-2 during the pandemic period and remains present at a considerable rate (~ 20%) [ 5 , 17 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As testing rules have eased or completely relaxed, asymptomatic patients or patients with symptoms that have not been tested or confirmed with COVID-19, can challenge the transmission of the virus amongst the most vulnerable. Moreover, the overall impact of respiratory virus co-infections in the present and upcoming seasons remains highly unknown in terms of morbidity burden, clinical severity, and outcome 8 . Though widespread testing of symptomatic individuals cannot be enforced nor justified, agreeing on a reasonable testing protocol for all respiratory viruses would make sense, especially within hospitals, so that we can identify coinfections and optimize treatment for patients.…”
Section: Priority 2: Testing and Diagnosismentioning
confidence: 99%